EFEKTIVITAS PELATIHAN “PERAN ORANG TUA DALAM MENDAMPINGI PENGGUNAAN GADGET ANAK” TERHADAP POLA INTERAKSI ORANG TUA-ANAK - Hidayat, Dyah Aji Jaya (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2022)
The use of gadgets that are less controlled among children causes anxiety for parents. It not only affects the academic value and personality of the child, but also on the interaction pattern of parents and children. This study aims to determine the effectiveness of the